An Exploration of Nene’ Mallomo’s Philosophical Values in Enhancing English Teachers’ Competence: A Study in Sidrap Regency - Nanning; Nur Asiza; Annisa Ahmad (Universitas Islam Negeri Palopo, 2025)
This qualitative descriptive study explores how the philosophical principles of Nene' Mallomo, an indigenous moral figure from Sidrap Regency, South Sulawesi, can enhance English teachers' personal competence through culturally grounded professional formation. Although personal competence is recognized as core to teacher professionalism in Indonesia, it remains underdeveloped and overshadowed by pedagogical and technical competencies. Ten English teachers from junior high schools in Sidrap Regency (n=10) were purposefully selected based on teaching experience and engagement with local cultural values. Data were collected through semi-structured interviews, field observations, and document analysis, then analyzed thematically to identify patterns in teachers' understanding, application, and challenges related to Nene' Mallomo's philosophy. Findings revealed deep familiarity with Nene' Mallomo's ethical principles—particularly honesty (malempu), consistency (getteng), intelligence (macca), and democratic fairness (temmapassilaingeng)—which teachers applied in assessment integrity, emotional regulation, equitable participation, and professional conduct. However, structural challenges, including grade inflation pressure, institutional inconsistency, and generational moral shifts, complicated value internalization. The study concludes that integrating Nene' Mallomo's philosophical values provides a culturally responsive framework for enhancing personal competence by uniting moral, spiritual, and intellectual dimensions of teacher professionalism. This research contributes to decolonizing teacher education by demonstrating that Indigenous moral wisdom can serve as a foundation for professional development in English language education.